Regulation and Role of Arabidopsis CUL4-DDB1A-DDB2 in Maintaining Genome Integrity upon UV Stress - Molinier, Jean (Public Library of Science, 2008)
Plants use the energy in sunlight for photosynthesis, but as a consequence are exposed to the toxic effect of UV radiation especially on DNA. The UV-induced lesions on DNA affect both transcription and replication and can also have mutagenic consequences. Here we investigated the regulation and the function of the recently described CUL4-DDB1-DDB2 E3 ligase in the maintenance of genome integrity upon UV-stress using the model plant Arabidopsis. Physiological, biochemical, and genetic evidences indicate that this protein complex is involved in global genome repair (GGR) of UV-induced DNA lesions. Moreover, we provide evidences for crosstalks between GGR, the plant-specific photo reactivation pathway and the RAD1-RAD10 endonucleases upon UV exposure. Finally, we report that DDB2 degradation upon UV stress depends not only on CUL4, but also on the checkpoint protein kinase Ataxia telangiectasia and Rad3-related (ATR). Interestingly, we found that DDB1A shuttles from the cytoplasm to the nucleus in an ATR-dependent manner, highlighting an upstream level of control and a novel mechanism of regulation of this E3 ligase.